2014
DOI: 10.1111/ggi.12360
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between each category of 25‐item frailty risk assessment (Kihon Checklist) and newly certified older adults under Long‐Term Care Insurance: A 24‐month follow‐up study in a rural community in Japan

Abstract: The physical strength category in men was the only significant predictor of the incidence of newly certified cases by LTCI. Further studies are required to improve the assessment item of cognitive function in KCL under LTCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
132
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 21 publications
1
132
0
Order By: Relevance
“…We identified that the majority of authors maintained the Japanese term "Kihon Checklist" 11,15,17,20,21 or used similar terms, "Kihon-Checklist" 22 and "Kihon Check Lists." 12 In addition, some authors translated and denominated the checklist as "Basic checklist for frailty"; 23 "Basic questionnaire" and "basic checklist";…”
Section: Kcl Terminologymentioning
confidence: 99%
See 4 more Smart Citations
“…We identified that the majority of authors maintained the Japanese term "Kihon Checklist" 11,15,17,20,21 or used similar terms, "Kihon-Checklist" 22 and "Kihon Check Lists." 12 In addition, some authors translated and denominated the checklist as "Basic checklist for frailty"; 23 "Basic questionnaire" and "basic checklist";…”
Section: Kcl Terminologymentioning
confidence: 99%
“…1,10 Furthermore, the next domain includes questions six to ten and has been named "physical strength domain," 11,15,20 "walking status domain," 14,23 "physical domain," 17 "motor function domain,"…”
Section: Kcl Terminologymentioning
confidence: 99%
See 3 more Smart Citations